2015
DOI: 10.1002/open.201402123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polarity and Activation Energy in Microwave-Assisted Organic Synthesis (MAOS)

Abstract: The aim of this work was to determine the parameters that have decisive roles in microwave-assisted reactions and to develop a model, using computational chemistry, to predict a priori the type of reactions that can be improved under microwaves. For this purpose, a computational study was carried out on a variety of reactions, which have been reported to be improved under microwave irradiation. This comprises six types of reactions. The outcomes obtained in this study indicate that the most influential paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 86 publications
(42 reference statements)
5
43
1
Order By: Relevance
“…These results are clearly compatible with our findings and show why the cyclization step must proceed at 140°C. In fact, the experimental activation energies obtained are in agreement with the observations of Rodríguez et al . who established that reactions with activation energies below 20 kcal⋅mol −1 occur easily by conventional heating, while reactions with activation energies above 30 kcal⋅mol −1 cannot be performed under conventional heating or need highly polar solvents under microwave irradiation.…”
Section: Resultssupporting
confidence: 90%
“…These results are clearly compatible with our findings and show why the cyclization step must proceed at 140°C. In fact, the experimental activation energies obtained are in agreement with the observations of Rodríguez et al . who established that reactions with activation energies below 20 kcal⋅mol −1 occur easily by conventional heating, while reactions with activation energies above 30 kcal⋅mol −1 cannot be performed under conventional heating or need highly polar solvents under microwave irradiation.…”
Section: Resultssupporting
confidence: 90%
“…The heating curve measured by the IR thermometers (external) is available in ESI † (SF 4-7). 22,30 To test the potential for MW-driven nucleation arising from the interaction of a MW photon with the molecular reactant, the heating behavior and VNA results for TOP-Te were analyzed. In BS the thermal lag is the same across all solvents; the rate of heating scales with the solvent tan d and is impacted to a lesser degree by thermal diffusivity (Fig.…”
Section: Mw Vessel Transparency Effects On Reaction Heating Ratesmentioning
confidence: 99%
“…17 Enhanced heating can occur due to MW-selective interactions with a susceptor, 18 solvent, polar molecule, or magnetic molecule, or to the influence of reduced thermal gradients and wall effects. 25, 30 Leadbeater measured the ability of molecules to thermalize in a solvent bath following MW photon absorption, and concluded that MW absorption leads to rapid thermal diffusion rather than directly enhancing a reaction path. [24][25][26] For instance, the use of different reaction conditions (pressure, temperature, time), solvents that absorb MW to various extents, different MW cavity designs, different MW energies, and reactor vessels made of different materials (quartz, glass, silicon carbide [SiC]) has complicated the discussion of MW enhancement of rates of reaction.…”
mentioning
confidence: 99%
“…This drawback of the solid-state S-alkylation reaction could not be circumvented by acting on the magnetic stirring of the MW source apparatus, since any increasing of the stirring speed produced the grinding of the resin beads (Rodriguez et al 2015).…”
Section: Resultsmentioning
confidence: 99%